Development of insulation material using bamboo fibers for thermal and sound properties - Mustafa, Mohd Syafiq Syazwan; Muhammad Syahroni, Badrun Muarrif; Rosli, Mohd Arif; Muhammad Damanhuri, Amir Abdullah; Zakaria, Anies Faziehan; Subri, Ummu Sakinah; Ahmad, Faridahanim (2024)
Currently, fiberglass is used as an insulation material, and this synthetic fiber is categorised as nonbiodegradable and causes air pollution. This study compared the thermal and acoustical properties of Betong bamboo (Dendrocalamus Asper) and fiberglass. Conductivity (K-Value) and sound absorption coefficient (SAC) were measured for both materials. The SAC was calculated using an impedance tube at low and high frequencies in accordance with EN ISO 10534-2:2001, while thermal conductivity was measured using Solteq HE110 thermal conductivity apparatus. From data analysis, the k-values of bamboo and fibreglass were 0.05 and 0.04, respectively. The analysis also showed that the difference in k-value between natural and synthetic fibers was 0.01 at 25 mm thickness, while fiberglass was 4.986. For sound acoustic, bamboo fibre showed 0.54 and 0.86 SAC between 2000 Hz and 2500 Hz, while 0.47 and 0.71 SAC were recorded for fibreglass. It can be concluded that bamboo fibre could be used as thermal and sound insulation, with performance equal to or better than fibreglass. Further research can be extended to make bamboo fibers as natural insulation for ducting, or in building. This study recommends refining bamboo fibres using different binders to increase durability and be used as insulation in the future